2020
DOI: 10.1096/fj.201902382r
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor 4α negatively regulates connective tissue growth factor during liver regeneration

Abstract: Liver regeneration after injury requires fine‐tune regulation of connective tissue growth factor (Ctgf). It also involves dynamic expression of hepatocyte nuclear factor (Hnf)4α, Yes‐associated protein (Yap), and transforming growth factor (Tgf)‐β. The upstream inducers of Ctgf, such as Yap, etc, are well‐known. However, the negative regulator of Ctgf remains unclear. Here, we investigated the Hnf4α regulation of Ctgf post‐various types of liver injury. Both wild‐type animals and animals contained siRNA‐mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 45 publications
(93 reference statements)
2
23
0
Order By: Relevance
“…YAP is an important regulator in liver regeneration following chemical and surgical‐induced damage. Consistent with our recent findings, 19 this study demonstrated Yap activation upon hepatocyte damage caused by insults such as ethanol and CCl 4 . Impaired regenerative responses were observed in hepatocyte‐specific Yap1 KO as summarized in Figure 7.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…YAP is an important regulator in liver regeneration following chemical and surgical‐induced damage. Consistent with our recent findings, 19 this study demonstrated Yap activation upon hepatocyte damage caused by insults such as ethanol and CCl 4 . Impaired regenerative responses were observed in hepatocyte‐specific Yap1 KO as summarized in Figure 7.…”
Section: Discussionsupporting
confidence: 93%
“…Hepatocyte damage and liver regeneration were induced through combined treatment with ethanol and CCl 4 according to our previous report. 19 Animals were allowed free access to diets with increasing concentrations of ethanol to 2% vol/vol (11% of Kcal) for 4 days. A single acute dose of CCl 4 (1 μl/g body weight) prediluted 1:3 in olive oil was given through intraperitoneal injection.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…HNF4-α is a YAP and TGF-β/SMAD3 antagonist; therefore, decreased expression of this molecule stimulates promitogenic functions and activates connective tissue growth factor. Increased HNF4-α expression during the subsequent phases of regeneration prevents the excessive synthesis of connective tissue and therefore fibrosis[ 70 ]. Hnf4-α also leads to the inhibition of HPC proliferation and migration in rats[ 71 ].…”
Section: Typical Liver Regenerationmentioning
confidence: 99%
“…As nuclear receptor transcription factors, HNF4 can directly regulate the transcription of the target gene by combining with the target gene promoter. HNF4α negatively regulated the transcription of CTGF by binding to its promoter during hepatocyte regeneration [ 39 ]. HNF4G activated the transcription of HAS2 by interacting with the promoter/enhancer region of HAS2 to promote the growth and invasion of bladder cancer cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%